MODERNISASI PENDIDIKAN PESANTREN DALAM PERSPEKTIF KH. ABDURRAHMAN WAHID - Muhammad Hasyim (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2016)
Pesantren is an islamic educational- institution that has the advantage of both aspects of scientific tradition and its transmission, as well as intensity of Muslims. Rise of globalization has threatened the existence of pesantren, so it causes the idea of ​​modernization in pesantren to address challenges of social transformation needs. To shape the direction of change in developing educational institutions, pesantren held their skills and enter the public schools into their environment. According to Gus Dur, pesantren should give an appreciation of all developments taking place in the present and future. However, in order to keep its traditions, pesantren should take on something new that is considered to be better and do not leave a long tradition. Entering the general sciences in pesantren’s environment has caused problems both among themselves and the public. The question is how exactly, epistemologically, explains the empirical sciences or secular sciences systematically into the pesantren’s tradition. According to Gus Dur, the idea to orient the contemporary pesantren may need to be reviewed because the idea will negatively affects the existence of the basic tasks of pesantren. In addition to strengthening the scientific tradition, pesantren should always open himself, accommodate the present problems, as well as providing enlightenment to the audience by giving the best solutions in resolving the problems of life. According to Gus Dur, boarding schools have relevance to the employment needs, for the world of work, both in services and trade with various needs expertise. Boarding schools must provide input for the education community about what skills are actually required by employment in the era of globalization such a rapid and diverse as it is today.